The influence of hydrophilic properties on the venting of foamy three phase systems. Issue 3 (23rd July 2013) - Leimeister, Henrik; Steinbach, Jörg
<x xml:space="preserve">Abstract</x> The correct design of a safety valve or rupture disk can only be done if predictions on the venting behavior can be made. To date, those predictions have limitations with regard to foaming or highly viscous systems. An experimental study is presented that describes the influence of hydrophilic particles on the venting of strongly and weakly foaming systems. It is shown that hydrophilic particles increase the mass discharge over time and reduce the pressure decrease over time by increasing the foaming of aqueous systems. These effects are not significantly influenced by the reactor characteristics. At higher additive concentrations, the addition of particles is not as influential anymore. Thus, models for foamy two‐phase systems are applicable for the design of the described foamy three‐phase systems as well. © 2013 American Institute of Chemical Engineers Process Saf Prog 32: 239–243, 2013